(untitled) (Update Dental College Journal, 2026)
Introduction: Significant adjustments in dental practice were required to reduce the risk of transmission during the COVID-19 pandemic since dental clinics are among the high-exposure settings. This study aimed to explore the modifications made in dental practice setups throughout the COVID-19 pandemic by the dental practitioners in Chattogram city of Bangladesh. Materials and Methods: A cross-sectional study was conducted among 96 dental practitioners in Chattogram city using a structured questionnaire. Data on patient screening and crowd control, infection control measures, hygiene practices, personal protective measures, and aerosol control strategies as well as practitioners’ demographics were collected. Descriptive statistics and Fisher’s exact test were used for analysis using SPSS. Results: Modal age 37.75±7.64 (27-70) years with a male-to-female ratio of 1.34:1. Two-thirds (66.67%) were dental graduates and majority (91.7%) worked in the private dental clinics. Commonly adopted safety practices included hand hygiene (100%), patient screening (84.4%), surface disinfection (95.8%), and social distancing (78.1%). High-volume suction was used by 61.5% of respondents, while advanced measures like HEPA filters (16.7%) and rubber dams (24.0%) were less frequently implemented. Statistically significant associations were found between age group and the use of face shields and vacuum suction (p <0.05). Conclusion: Dental practitioners in Chattogram city demonstrated commendable efforts in modifying their clinical practices during the COVID-19 pandemic. However, the limited use of advanced aerosol control measures highlights the need for better resource access and institutional support. Continued education and national guidelines are recommended to strengthen pandemic response in dental settings. Update Dent. Coll. j: 2025; 15(2): 21-26